Susceptibility or resistance to lysis by alloreactive natural killer cells is governed by a gene in the human major histocompatibility complex between BF and HLA-B. - Ciccone, E (1990)
The specificity recognized on normal allogeneic cells by a given alloreactive (1-anti-A) natural killer clone is controlled by a gene locus termed EC1. Because the EC1 locus was previously shown to be located on chromosome 6, families characterized by a recombinant major histocompatibility complex haplotype were analyzed to map this locus more precisely. The breakpoint of recombination was studied by standard HLA typing, complement typing, and restriction fragment length polymorphism analysis of a series of genes located between the complement cluster genes and HLA-B within the major histocompatibility complex region. Three of 10 families analyzed were informative. From the data obtained, the EC1 locus maps between BF and HLA-B and presumably is one of the normal genes recently described in this region.